A relação entre a noção de justiça (dikaiosūnē)e a teoria das Formas na República de Platão - Carneiro, Gabriela Carvalho (2017)
The main objective of this research is to relate the definition of dikaiosūnē in Plato’s Republic to the Theory of Forms. In order to do that, an analysis of the various areas of knowledge in Plato is necessary, since he does not separate the areas of knowledge as the modern scholars usually do. The main theme in the Plato’s Republic is dikaiosūnē (justice). In pursuing a definition of justice that refutes, in a satisfactory way, the definition of Thrasymachus, Plato develops one of his most daring theories. Arguing against Thrasymachus, and answering fundamental questions proposed in the course of this dialogue (what justice is and if justice is more advantageous than injustice), Socrates proposes a new model of polis education. This model of education is based on a theory of psūchē formation, a metaphysics, a morality and an epistemology. In the Republic, one can note that Plato is interested in producing a theory and also a definition of dikaiosūnē that covers different situations. Since the construction of the definition of dikaiosūnē must be present in something that is fair in any situation, it can be said that the only means for this is to suppose a notion of Form of justice that can be applied in different cases, time and objects/individuals. It is important to note that one of the main theses of the Republic is the proposition that ethics and political theory require members of the polis to think and act on the basis of correct ethical judgments. Such judgments should have entities that are sufficiently fixed, stable and determined, which means, for Plato, that it should have Forms as their base. So, we can affirm that even if there is no instance of justice in the world, the Form of justice will be theret. This Justice, however, will be represented and expressed only in the well-ordered polis, the one governed by individuals who have knowledge of the Forms and govern the city in a way they imitate the Forms. This seems to us one a clear sign that there is in the Republic a Form of Justice.